Speciation with gene flow via cycles of isolation and migration: insights from multiple mangrove taxa - He, Ziwen (Natl Sci Rev, 2019)
Allopatric speciation requiring an unbroken period of geographical isolation has been the standard model of neo-Darwinism. While doubts have been repeatedly raised, strict allopatry without any gene flow remains a plausible mechanism in most cases. To rigorously reject strict allopatry, genomic sequences superimposed on the geological records of a well-delineated geographical barrier are necessary. The Strait of Malacca, narrowly connecting the Pacific and Indian Ocean coasts, serves at different times either as a geographical barrier or a conduit of gene flow for coastal/marine species. We surveyed 1700 plants from 29 populations of 5 common mangrove species by large-scale DNA sequencing and added several whole-genome assemblies. Speciation between the two oceans is driven by cycles of isolation and gene flow due to the fluctuations in sea level leading to the opening/closing of the Strait to ocean currents. Because the time required for speciation in mangroves is longer than the isolation phases, speciation in these mangroves has proceeded through many cycles of mixing-isolation-mixing, or MIM, cycles. The MIM mechanism, by relaxing the condition of no gene flow, can promote speciation in many more geographical features than strict allopatry can. Finally, the MIM mechanism of speciation is also efficient, potentially yielding m(n) (m > 1) species after n cycles.